Analisis Pengaruh Jam Kerja Terhadap Beban Kerja Mental Dengan Metode Subjective Workload Assessment Technique - Rahul Ray; Yetti Meuthia Hasibuan; Denny Walady (CV. IRA PUBLISHING, 2023)
This research contains a study of the effect of working hours on mental workload using the Subjective Workload Assessment Technique (SWAT) method. Workload is a consequence of activities given to workers, worker activities can basically be distinguished between physical activities and mental activities. In practice, the workload encountered is a combination of physical workload and mental workload. This study aims to measure mental workload at 10 work stations in the production section at PT Berlian Eka Sakti Tangguh. The SWAT method is a subjective mental workload measurement method based on workers' perceptions. The dimensions are time load, mental effort load and psychological pressure load. The results of the calculation of workload based on SWAT found that the workload category of workers in the production section is at a moderate and high level. The highest workload was experienced at the palm oil storage station (5 workers) at 83.71%. The lowest workload was experienced at the stewing station (3 workers) at 27.36%.